Sosyal bilgiler öğretmenliği lisansüstü programları akreditasyon standart-gösterge ve kanıtlarının belirlenmesi - Elçiçeği, Büşra (My University, 2022)
Akreditasyon yetki, yeterlik ve güvenirliğin onaylandığı sertifikalı bir kalite güvence sistemi ve sürecidir. Akreditasyon süreci; Türkiye ve dünyada yükseköğretim kurumlarında (lisans ve lisansüstü programlarda) nitelik ve niceliğin iyileĢtirilmesine hizmet ederek kalite güvencesini sağlamaktadır. Ulus devletler farklı ülkelerin ilk, orta ve yükseköğretim kurumlarından mezun olmuĢ bireylerle daha güçlü bir Ģekilde rekabet edebilen mezunlar yetiĢtirmeye odaklanmıĢtır. Eğitim sistemlerini yönlendiren önemli geliĢmelerden biri olan küreselleĢme kavramı sonucunda ülkeler arasında yükseköğretim kurumlarında rekabet artmıĢ ve yükseköğretim kurumu ile bu kurumlarda eğitimi gerçekleĢtirilen programların kalitesinin arttırılmasına yönelik giriĢimler yaĢanmıĢtır. Yükseköğretim kurumları küreselleĢmenin getirmiĢ olduğu değiĢim ve yenilikler temelinde hızlı bir Ģekilde bilgi ve biliĢimin sürekli olarak üretildiği ve dönüĢtürüldüğü ulusal/ uluslararası boyutta çok yönlü bir çevresel etkileĢimin yaĢandığı kurumlar hâline dönüĢmüĢtür. Bu doğrultuda yükseköğretim kurumlarının, araĢtırmalar aracılığıyla bilgi üretme, eğitim ve öğretim faaliyetleri kapsamında gelecek nesillere bilgi aktarımında bulunma, toplumsal ihtiyaç ve beklentilere uygun hizmetler üretme gibi fonksiyonları ortaya çıkmıĢtır. Yükseköğretim kurumlarına bağlı enstitülerde gerçekleĢtirilen lisansüstü eğitim ise uluslararasılaĢma faaliyetlerinde önemli bir misyona sahiptir. Lisansüstü çalıĢmalara yön veren enstitüler (Sosyal Bilimler, Fen Bilimleri, Sağlık Bilimleri, Eğitim Bilimleri x Enstitüleri) tarafından koordine edilen lisansüstü eğitim, yüksek lisans ve doktora programları ile birlikte tıpta uzmanlık, sanatta yeterlik alanlarını kapsamaktadır. Lisansüstü eğitim, bir lisans programından mezun olmuĢ adaylara, bir bilim dalında uzmanlaĢma olanağı sağlayan yüksek lisans (bilim uzmanlığı) ve doktora öğrenimi olmak üzere iki aĢamalı bir öğrenim sürecidir. Yüksek lisans eğitimi kendi içerisinde programın özelliğine göre tezli ve tezsiz yüksek lisans olarak ikiye ayrılmaktadır. Doktora programında ise adaylar eğitim sürecini tamamladıktan sonra doktora tezlerini savunmalarının ardından doktor unvanına sahip olmaktadır. Türkiye‟de herhangi bir alanda lisansüstü akreditasyon faaliyetleri yürütülmemektedir. Ülkemizde genel olarak eğitim bilimleri enstitülerine bağlı lisansüstü programlarda (öğretmenlik mesleğine iliĢkin programlar) özelde Sosyal Bilgiler Eğitimi Lisansüstü Programlarının akreditasyon faaliyetlerinin bulunmaması nedeniyle bu çalıĢma “Sosyal Bilgiler Öğretmenliği Lisansüstü Programları akreditasyon standart, gösterge ve kanıtlarının belirlenmesi” amacıyla yapılmıĢtır. Bu çalıĢma nitel ve nicel araĢtırma yöntemlerinin veri toplama araçları ve veri analiz tekniklerinin ikili kombinasyonu kullanılarak gerçekleĢtirilmiĢtir. AraĢtırmanın çalıĢma grubunu Türkiye‟de eğitim fakültesi programlarının akreditasyon faaliyetlerini yürüten tek kurum olan Öğretmenlik Eğitim Programları Değerlendirme ve Akreditasyon Derneğinin (EPDAD) özellikle Sosyal Bilgiler eğitimi alanında olmak üzere eğitim programları, ölçme-değerlendirme ve çeĢitli branĢlarda kadrosu bulunan ve EPDAD‟ın akreditasyon faaliyetlerinde değerlendirici olarak görev alan öğretim elemanları ve lisansüstü öğrenciler ile akreditasyon süreçlerine dâhil olmamıĢ akademisyenler ve akreditasyon sürecinin bir parçası olan MEB uygulama okullarında görev yapan lisansüstü öğrenim gören öğretmenler oluĢturmaktadır. Bu Ģekilde akreditasyon süreçlerine dâhil olan ve olmayan iki grubun görüĢ, öneri ve beklentileri karĢılaĢtırmalı olarak ele alınmıĢtır. Ayrıca MEB uygulama okullarındaki öğretmenlerin ve lisansüstü öğrencilerin de çalıĢmaya dâhil edilmesi ile olabildiğince tüm paydaĢlar sürece dâhil edilmiĢ ve bunların değerlendirmeleri analiz edilmiĢtir. 4 aĢamalı olarak gerçekleĢtirilen bu çalıĢmanın ilk aĢamasında, Türkiye ve dünyada faaliyet gösteren akreditasyon kurumlarının sürece yönelik belgelerine (tüzükleri, standartları, uygulama örnekleri vb.) doküman incelemesi tekniği doğrultusunda ulaĢılarak incelenmiĢ, dokümanların gerekli dillerden Türkçeye transkripsiyon çevirisi yapılmıĢ ve elde edilen veriler sentezlenip amaca hizmet eden araca dönüĢtürülerek Sosyal Bilgiler öğretmenliği lisansüstü programları için akreditasyon standartları hazırlanmıĢtır xi ÇalıĢmanın ikinci aĢamasında hazırlanan Sosyal Bilgiler öğretmenliği lisansüstü programları akreditasyon standartları (8 standart alanı ve alt standartları) Delphi tekniği aracılığıyla katılımcılara sunulmuĢ ve uzman görüĢleri elde edilmiĢtir. I. Delphi turunda katılımcılardan elde edilen yanıtlara iliĢkin güvenirlik analiz sonucu 0.933 iken II. Delphi turu Cronbach‟s Alpha değeri 0.991‟dir. Bu değerin 0.90‟nın üzerinde olması mükemmel güvenirliğin göstergesidir. Üçüncü aĢamada üzerinde uzlaĢılan Sosyal Bilgiler Öğretmenliği Lisansüstü Programları standartlarının lisansüstü eğitimden sorumlu olan enstitülerin programında nasıl yer edineceği belirlenmiĢ, son aĢamada ise incelenen akreditasyon kurumlarının dokümanları örnek alınarak Sosyal Bilgiler öğretmenliği lisansüstü programları akreditasyon standartlarının göstergeleri ve kanıtları hazırlanmıĢtır. Hazırlanan gösterge ve kanıtların güvenilirliğini sağlamak için uzman görüĢüne baĢvurulmuĢtur. Delphi tekniği, aynı anketin bir uzman grubuna birden fazla uygulanması ile gerçekleĢtirilen bir tekniktir. Bu doğrultuda araĢtırmacı tarafından hazırlanan anket gözden geçirilerek üç kez katılımcılara uygulanmıĢtır. Doküman incelemesi tekniği kapsamında ENQA, EQAA, EQAR, ESU, INQAAHE, CEENQA vb. kuruluĢlara üye olan/ olmayan Türkiye ve dünyadaki mevcut akreditasyon kurumlarının yapısı, amaçları, akreditasyon dereceleri [lisans, lisansüstü (yüksek lisans/ doktora)], standartları ve kanıtları karĢılaĢtırmalı olarak incelenmiĢtir. Delphi ve doküman incelemesi teknikleri sonucunda elde edilen verilerdeki kavram ve temalar, içeriğin belirlenmesi aĢamasında yorumlamanın yapıldığı betimsel analiz tekniği ile çözümlenmiĢ ve son aĢamada Türkiye‟de lisansüstü akreditasyon faaliyetlerinin baĢlayarak eğitimde nitelik artıĢının yaĢanması için kullanılabilecek örnek lisansüstü standart, gösterge ve kanıtlar oluĢturulmuĢ, uygulamaya yönelik öneriler yapılmıĢtır. Sosyal Bilgiler Eğitimi, Lisansüstü Eğitim, Akreditasyon,

Determinatıon of Standards-Indicators and Evidence for Social Studies Education Graduate Programs Accreditatıon Accreditation is a certified quality assurance system and process that confirms authority. Accreditation process provides quality assurance by serving to improve quality and quantity in higher education institutions (undergraduate and graduate programs) in Turkey and in the world. Nation states have focused on producing graduates who can compete more strongly with individuals who have graduated from primary, secondary and higher education institutions of different countries. As a result of the concept of globalization, which is one of the important developments that directs education systems, competition in higher education institutions has increased among countries and attempts have been made to increase the quality of higher education institutions and programs taught in these institutions. Higher education institutions have quickly turned into institutions where information and informatics are constantly produced and transformed on the basis of the changes and innovations brought by globalization, where a multi-faceted environmental interaction is experienced on a national/ international scale. In this direction, functions of higher education institutions such as producing knowledge through research, transferring knowledge to future generations within the scope of education and training activities, and producing services in accordance with social needs and expectations have emerged. Graduate education carried out in institutes affiliated to higher education institutions has an important mission in internationalization activities. Graduate education coordinated by institutes (Social Sciences, Sciences, Health Sciences, Educational Sciences Institutes) that direct graduate studies includes master's and doctorate programs as well as specialization in medicine and proficiency in art. Graduate education is a two-stage learning process, namely master's (science specialization) and doctorate education, which provides opportunity to specialize in a field of science for candidates who have graduated from an undergraduate program. Master's education is divided into two as master's with thesis and without thesis, according to characteristics of the program. In doctoral program, after completing the education process, candidates have the title of doctor after defending their doctoral thesis. xiii Graduate accreditation activities are not carried out in any field in Turkey. This study was carried out with the aim of determination of the standards, indicators and evidence for the accreditation of the Social Studies teaching graduate program, since there are no accreditation activities for Social Studies education graduate program in private sector in graduate programs (programs related to the teaching profession) affiliated to educational sciences institutes in general in our country. This study was carried out using a dual combination of data collection tools and data analysis techniques of qualitative (literature review, document review) and quantitative (survey) research methods. The study group of the research consisted of evaluators in EPDAD's accreditation activities, which has staff in education programs, measurement-evaluation and various branches, especially in the field of Social Studies Education, in Association for the Evaluation and Accreditation of Teacher Education Programs (EPDAD), which is the only institution in Turkey that carries out the accreditation activities of the programs of education faculties, and academic staff and graduate students who work as faculty members, academicians who are not involved in accreditation processes, and graduate teachers working in MEB practice schools that are part of the accreditation process. In this way, opinions, suggestions, and expectations of two groups that are involved in the accreditation processes and those that are not involved were discussed comparatively. In addition, all stakeholders were included in the process by including teachers and graduate students in MEB practice schools in the study their evaluations were analyzed. In the first stage of this study, which was carried out in 4 stages, the documents of the accreditation institutions operating in Turkey and in the world regarding the process (statutes, standards, application examples, etc.) were accessed and examined in accordance with the document analysis technique, the documents were transcribed from the required languages into Turkish and obtained data were synthesized and transformed into tool serving into purpose, and Social Studies teacher graduate accreditation program standards were prepared. In the second phase of the study, the standards of the Social Studies teaching graduate accreditation program (8 standard areas and sub-standards) were presented to the participants through the Delphi technique and expert opinions were obtained. While the reliability analysis result of answers obtained from the participants in I. Delphi round was 0.933, II. Delphi round Cronbach's Alpha value was 0.991. A value above 0.90 indicates excellent reliability. In the third stage, it was determined how agreed Social Studies teaching graduate program standards would take place in the programs of xiv the institutes responsible for graduate education, and in the last stage, indicators and proofs of Social Studies teaching graduate accreditation program standards were prepared by taking documents of accreditation institutions examined as an example. Delphi technique is a technique performed by applying same questionnaire to a group of experts more than once. Expert opinion was sought to ensure the reliability of the prepared indicators and evidence. In this direction, the questionnaire prepared by the researcher was reviewed and applied to the participants three times. Within the scope of document review technique, structure, objectives, accreditation degrees (undergraduate, graduate (master's/ doctorate)), standards and evidence of existing accreditation institutions in Turkey and in the world, which are members to institutions such as ENQA, EQAA, EQAR, ESU, INQAAHE, CEENQA or not were examined comparatively. The concepts and themes in the data obtained as a result of Delphi and document analysis techniques were analyzed with the descriptive analysis technique, in which interpretation was made at the stage of determining the content, and at the last stage, sample graduate standards, indicators and evidence that can be used to increase the quality of education by starting graduate accreditation activities in Turkey were created, and practical suggestions were made. Social Studies Education, Graduate Education, Accreditation, Turkey
Determination of standards-indicators and evidence for social studies education graduate programs accreditation
Keywords: Accreditation; Akreditasyon; Graduate Education; Lisansüstü Eğitim; Öğrenim ve öğretim; Social science; Sosyal Bilgiler Eğitimi; Sosyal bilimler; Study and teaching; Turkey; Türkiye Social Studies Education